Dylematy etyczne dziennikarstwa politycznego - Palczewski, Marek (Polityka i Społeczeństwo, 2020)
The Article concerns the ethical dilemmas faced by political journalists. This problem has been discussed in the context of the complaints which have been considered by the Council of Ethics of the Media, the decisions of the Commission of Ethics in TVP, as well as on the example of several case studies, in which some abuses of journalistic ethics are stated. The method of analysis was a content analysis. With the presented analysis of complaints and matters relating to political journalists, it appears that journalists violate ethical standards: manipulate facts and images, use rumours and unverified information, affecting the personal rights and the privacy of non-executive public, do not respect the principles of objectivity and impartiality. There are, however, situations when journalists have suffered punishment in the form of dismissal, even though they acted in accordance with ethical principles. In conclusion, the dilemmas of political journalists can be divided into: (1) professional (2) relational, (3) newsrooms, and (4) dilemmas of conscience.